The Patient Health Questionnaire-9 (PHQ-9) as a brief screening tool for depression: a study of Iranian college students. Issue 8 (14th September 2021) - Dadfar, Mahboubeh; Lester, David; Hosseini, Agha Fatemeh; Eslami, Monireh
ABSTRACT: The aims of the present study were (a) to investigate the psychometric properties and to explore the factorial structure of the Patient Health Questionnaire-9 (PHQ-9), (b) to explore the association of PHQ-9 scores with Loneliness Scale (LS) scores, (c) to determine the severity of symptoms of depression, and (d) to examine sex differences. The PHQ-9 and LS were administered to a convenience sample of 260 Iranian university students. Cronbach's α was .84 for the PHQ-9. Two factors were extracted labelled "Affective", and "Somatic/Vegetative." PHQ-9 scores correlated positively (r = .57) with LS scores. Suicidal ideation was predicted by both factors of the PHQ-9 and by their LS scores. Sixty-nine percent of the students experienced mild to severe depression, and the men and women did not differ significantly in scores. This study can provide data points for meta-analyses and may help to determine social, cultural or economic conditions influencing student depression.